Uma Análise do Capital Social no Arranjo Produtivo Local do Leite de Santana do Livramento - Tiago Zardin Patias (Universidade Regional do Noroeste do Estado do Rio Grande do Sul, 2015)
The dynamics of economic environment requires that companies seek sustainable competitive ad - vantages as a strategy to survive in the competitive market. Arise in this context the Local Productive Arrangements (LPAs) as a means to increase competitiveness and local and regional social capital. The present study aims to determine the social capital of LPA of milk from Santana do Livramento - -RS, identifying which variables influence their formation and propose actions to empower them. It is characterized as a quantitative descriptive research, collecting data through a survey with a sample of rural milk producers belonging to LPA. It is inferred that in the present milk LPA, the social capital, measured by the structural, cognitive and relational dimensions, has positive elements, such as trust, social identity and participation, which require maintenance. It is also identified negative elements such as social relations among the producers, low cooperation, reciprocity and the need for greater interaction.